Internet access as a fundamental right and structural discrimination: inter-American standards of protection - Leal, Mônia; Crestane, Dérique (UNIO – EU Law Journal, 2025)
The advance of information technology, coupled with the dissemination of electronic devices that enable access to it, has made it a central element in human life, placing access to the Internet as a core aspect of the exercise of fundamental freedoms and rights, as well as citizenship itself. However, it has been observed that certain groups, associated with structural factors of inequality, may have increased difficulties in accessing the web, a phenomenon known as the “digital divide”, thus tending to accentuate existing discrimination. In this context, this text seeks to answer the question of whether the constitutional courts of Latin American countries recognise Internet access as a fundamental right – and if so, whether it is an autonomous or instrumental fundamental right. It also seeks to find out whether it is possible to identify any approach to the elements of structural discrimination in these judicial decisions.